Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754794
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Adaptive Search from Random Search in Robots and T cells

Abstract: In order to trigger an adaptive immune response, T cells move through lymph nodes (LNs) searching for dendritic cells (DCs) that carry antigens indicative of infection. We hypothesize that T cells adapt to cues in the LN environment to increase search efficiency. We test this hypothesis by identifying locations that are visited by T cells more frequently than a random model of search would suggest. We then test whether T cells that visit such locations have different movement patterns than other T cells. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Desert plants accelerate soil respiration in response to brief episodes of rainfall (Potts et al, 2014). Cytokines create chemical interactions that T cells follow, with the outcome that numbers of T cells increase at a location where pathogens are patchy and concentrated in time and space (Fricke et al, 2015;Chao et al, 2004). An interesting question is whether the reverse is also true.…”
Section: Algorithms Shaped By the Distribution Of Resourcesmentioning
confidence: 99%
“…Desert plants accelerate soil respiration in response to brief episodes of rainfall (Potts et al, 2014). Cytokines create chemical interactions that T cells follow, with the outcome that numbers of T cells increase at a location where pathogens are patchy and concentrated in time and space (Fricke et al, 2015;Chao et al, 2004). An interesting question is whether the reverse is also true.…”
Section: Algorithms Shaped By the Distribution Of Resourcesmentioning
confidence: 99%
“…A key feature that influences search strategy is the distribution of resources in time and space (36, 3840). Targets can be patchy, clustered into one location, or dispersed uniformly at random through the entire search area.…”
Section: Ant Foraging As a Model For T Cell Searchmentioning
confidence: 99%
“…In [61,62], the authors proposed a search strategy for a team of mobile robotic sensors based on the T cell movement in lymph nodes and they showed that the distributions of the step-sizes taken by T cells are best described by a random walk with the Levy-like distribution. In [162], a bio-inspired random search strategy for the multi-robot system to efficiently localize targets in underwater search scenarios was proposed.…”
Section: Distributed Bio-inspired Random Search For Locating Static T...mentioning
confidence: 99%
“…The process of evolution and natural selection has led animals to optimize their foraging strategies. As a result, in recent years, many search algorithms have been inspired by the Levy walk random search method [61,62].…”
Section: Distributed Bio-inspired Algorithm For Search Of Moving Targetsmentioning
confidence: 99%